Inovasi dan Efisiensi: Pendampingan Usaha UMKM DAPOERUWIK.ID Di Kota Mojokerto - Haryawan, Beny; Basuni, Basuni; Hermawan, Agus (Penamas: Journal of Community Service, 2025)
DAPOERUWIK.ID, located in the City of Mojokerto, is a business engaged in the culinary field, specifically in the production of cakes and pastries. With the main challenges being the limitations of digital marketing strategies, product design, and operational efficiency, this community service activity aims to provide support based on innovation and efficiency. The methods used include individual approaches, training, and the creation of a sustainable master plan. The results include the development of visual communication design, social media-based marketing strategies, and product innovation through vacuum pack packaging. This article documents the positive impact of mentoring on the development of the DAPOERUWIK.ID business.